THE FEATURES OF MATHEMATICAL MODELING OF GROUND FLOW FOR URBAN TERRITORIES (ON AN EXAMPLE OF GOLOSIIVSKA AREA IN KYIV) - KOSHLIAKOV, O.; MANDRYK, B. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The given features of mathematical modeling of ground flow for urban territories on an example of Golosiivska area in Kiev. The technique of definition and correcting initial circuits of ground flows behind indirect attributes is offered.